The new economic era analysis of the structure system of Chinese household consumption expenditure based on the ELES model - Fan, Chaozhi; Law, Siong Hook; Ibrahim, Saifuzzaman; Naseem, N. A. M. (Hindawi, 2022)
In recent years, the new economy has entered a phase of rapid development and upgrading China’s service consumption is driving the continuous optimization of the population’s consumption structure. To realize the rationalization of the Chinese household consumption structure, the ELES model is used to analyze the structure system of Chinese household consumption expenditure. This article constructs the ELES model, divides the types of Chinese household consumption expenditure structure systems, establishes consumption expenditure function, analyzes the influencing factors of the consumption expenditure structure system, and obtains the analysis results from static and dynamic aspects. Based on the statistics of Chinese household consumption expenditure data in recent years, this article obtains the analysis results of the consumption expenditure structure system: the basic consumption demand and marginal consumption tendency of food are in the first place, and the consumption expenditure structure system has gradually changed into the development-type and enjoyment-type consumption mode. Through increasing the income of rural residents, guiding reasonable consumption concept, optimizing consumption environment, and so on, we can promote the proposal and implementation of the optimization of China’s household consumption expenditure structure system to improve the rationalization of China’s household consumption structure system.